Theory of Symbols by the second generation of Russian Symbolists & the Archetypal Theory: Religious, Anthropologic, Cultural Aspects of Succession - S. N. Lyutova (Vestnik MGIMO-Universiteta, 2012)
The article is about the Theory of Symbols by second generation of Russian Symbolists and the Archetypal Theory. Both of theories were researched as related religious and philosophical forms of the XXth cent. Western civilization crisis reflection and as attempts to foresee the ways of European mentality transformation. Admitting common cultural genesis of the theories, the author determined Jungian Archetypal Theory in succession to the Theory of Symbols by Andrey Bely. Also the author traced development of several of the Russian Modern Anthropological ideas at the American Post-modern Cultural Anthropology.